2000
DOI: 10.1111/j.1471-0528.2000.tb11658.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac troponin I in pre‐eclampsia and gestational hypertension

Abstract: Objective To investigate serum cardiac troponin I, a sensitive marker of cardiac rnyocyte damage, in normal pregnancy and pregnancies complicated by hypertension with and without significant proteinuria.Design Prospective cross sectional study.Setting University hospital delivery suite.Sample Serum samples obtained from women in normal pregnancy and in pregnancies complicated by hypertension with and without significant proteinuria.Method Women with hypertension in pregnancy (at least two readings of systolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0
5

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 332 publications
(53 citation statements)
references
References 20 publications
0
48
0
5
Order By: Relevance
“…The normotensive group were non-proteinuric patients with uncomplicated pregnancies. The criteria for pre eclampsia were as follows: at least two separate blood pressure readings O 140/90 mmHg, and the presence of C1 protein or more, by dipstick analysis on more than one occasion (Fleming et al 2000). Women with known pre existing cardiac or renal disease were excluded from the study.…”
Section: Tissue Collectionmentioning
confidence: 99%
“…The normotensive group were non-proteinuric patients with uncomplicated pregnancies. The criteria for pre eclampsia were as follows: at least two separate blood pressure readings O 140/90 mmHg, and the presence of C1 protein or more, by dipstick analysis on more than one occasion (Fleming et al 2000). Women with known pre existing cardiac or renal disease were excluded from the study.…”
Section: Tissue Collectionmentioning
confidence: 99%
“…Cong et al have reported that cardiac remodeling occurs in patients with preeclampsia, and is associated with eccentric myocardial hypertrophy, with reduced EF [18]. Indeed, cTnI values measured during gestational hypertension and preeclampsia show higher values in the latter [7]. But it is also evident that not all patients with preeclampsia demonstrate a significant rise in cTnI or whether cTnI levels increase during the course of the disease and are affected by the increasing severity of the disease [16,19].…”
Section: Discussionmentioning
confidence: 95%
“…Lastly, elevation of cTnI in hypertensive disorders of pregnancy is well reported, although the cause remains unclear [7,[12][13][14][15]. Fleming et al demonstrated five-fold higher values of cTnI in preeclamptic women than in normotensive pregnant women, indicating possible subclinical cardiac myofibrillatory damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Troponin levels have also been studied during pregnancy and are generally felt to remain in the normal range, but they may rise to the upper limit of normal. 7,8 Like BNP, troponin levels are higher in women with hypertensive disorders of pregnancy, particularly pre-eclampsia.…”
Section: Information About a Real Patient Is Presented In Stages (Bolmentioning
confidence: 99%